2009
DOI: 10.1002/pssa.200881156
|View full text |Cite
|
Sign up to set email alerts
|

Spatially resolved characterization of chemical species and crystal structures in CuInS2 and CuGax Sey thin films using Raman microscopy

Abstract: This study demonstrates the potential of Raman microscopy in the analysis of thin film cross‐sections. Raman maps of the photovoltaic material CuInS2 (CIS), which was prepared by the spray ion layer gas reaction method, revealed the spatial distribution of two different CIS modifications – chalcopyrite‐type and CuAu I‐type CIS – as well as contaminants and segregates with a lateral resolution of approx. 400 nm. Additionally, the chemical heterogeneity of a CuGaSe2/CuGa3Se5 bi‐layer stack was clearly resolved. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…Furthermore, we often detected two broad bands centered at ~1322 cm −1 and ~1605 cm −1 (see Fig. S4, Supporting Information), which can be assigned to the D and G band, respectively, of amorphous carbon (compare, for example, the carbon spectra in Refs , which we consider the main coloring component of the black slag particles we found in several cement‐bound artificial stone samples taken from Swiss buildings from the late 19th and early 20th century. In contrast to the typical irregular shape of slag particles described in polarizing light microscopy studies, we found slag only in the form of black spheres with diameters of up to 500 µm (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…Furthermore, we often detected two broad bands centered at ~1322 cm −1 and ~1605 cm −1 (see Fig. S4, Supporting Information), which can be assigned to the D and G band, respectively, of amorphous carbon (compare, for example, the carbon spectra in Refs , which we consider the main coloring component of the black slag particles we found in several cement‐bound artificial stone samples taken from Swiss buildings from the late 19th and early 20th century. In contrast to the typical irregular shape of slag particles described in polarizing light microscopy studies, we found slag only in the form of black spheres with diameters of up to 500 µm (Fig.…”
Section: Resultsmentioning
confidence: 84%
“…For a compositionally inhomogeneous layer, this implies that adjacent regions of different composition in the layer might contribute to the spectrum measured with the laser spot at a given position. Higher in-depth resolution (about 400 nm) has been achieved by the combined AFM/Raman microprobe mapping of cross sections of samples prepared in the form of standard TEM specimens [32]. Another option is the use of an Ar þ ion beam for the selective sputtering of the layer to different depths [33]: this allows us to obtain a depth resolution of the order of 100 nm because of the high light absorption of these semiconductors.…”
Section: Chemical Analysis Of Semiconducting Alloysmentioning
confidence: 99%
“…Raman peaks around 337−345 cm −1 were assigned to the modes of CH E LO 1 and CH B 2LO 1 . 34,36 These results indicate that the precursors did not undergo structural ordering to provide stoichiometric chalcopyrite CIS at low temperatures. The Raman spectra were deconvoluted by assuming Gaussian peak functions (see Figure S1 in the Supporting Information).…”
Section: Resultsmentioning
confidence: 85%